The Flash. The complete third season [videorecording (DVD)] - Warn, Jesse; Hemecker, Ralph; Gustin, Grant, 1990-; Patton, Candice; Panabaker, Danielle (Warner Bros. Entertainment, 2017)
After an accident with a particle accelerator gives Barry Allen super powers, he becomes the Flash and uses his power to fight crime.